RANCANGAN SISTEM KEAMANAN LOKER PADA ALAT PENGISI BATERAI GADGET UNTUK FASILITAS UMUM:E-LOCKER - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
In this research, RFID is used as an electronic key opener safety deposit box (locker) which exist in the location (public areas) , such as equipment filler battery on electronic devices gadgets using solar energy , thus the resources of electronic lock uses battery filled through solar. System electronic lock solenoid doorlock working with RFID tag and RFID reader with Arduino UNO. From the test results, the RFID tag can recognize RFID reader with a reading at a distance of 6 cm. The results of this study applied to the locker battery gadget charger with solar energy.